Stan Naprężenia w Tarczy Kolistej Wywołany Działaniem Źródła Ciepła - Piechocki, W. (Engineering Transactions, 1958)
The aim of this paper is to determine the stress isotropic disc by the action o galvanised in a circular chosen fa heat source W located at an arbitrarily point. The solution of the problem (the determination of the state of stress due Green's function) enables us to determine, by means of integration, to heat source distributed along the line L, or over the region S of the plate. The so-called potential of thermoelastic dis- placement is used. The displacement for plane stress (1.2), and that equation of the theory of elasticity replaced by the for steady temperature field (1.1), are of the stresses unique equation (1.3). The boundary conditions are those of the stresses σrr and  σrϕ, becoming zero for r = r0. The any value on the boundary. The temperature is determined additional state of stress σik is determined by means of the Airy function. The result of super-position of σik and σik is obtained in a closed form. In addition, the so is obtained for k identical sources. It is shown that in the particular case where a -> 0, the solution of Melan and Parkus is obtained.